High-risk subtype: Clinical manifestations and molecular characteristics of submandibular gland adenoid cystic carcinoma - Zhou, Mengjiao; Ma, Tingyao; Wang, Xuelian; Zhang, Shujing; Yang, Guoliang; Song, Ruohui; Chen, Xiaohong (Frontiers in Oncology, 2022)
Objective Adenoid cystic carcinoma of the head and neck mainly occurs in the major salivary glands, of which the parotid gland and submandibular gland are the most common. The purpose of this study was to clarify the site-specific differences in prognosis and molecular expression characteristics of the patients and to achieve stratified risk management of the clinical prognosis. Materials By performing a single-centre retrospective analysis combined with analyses of the Surveillance, Epidemiology, and End Results (SEER) database, cBioPortal and GEO databases, the clinical prognostic characteristics and the differences in molecular expression patterns of ACC in the submandibular gland and parotid gland were analysed. Cox regression analysis, the chi-square test, Fisher’s test and the log-rank test were used to compare the significance of differences. Results Compared with patients with parotid gland ACC, the submandibular gland ACC is more likely to have metastases in the cervical lymph node (21.7% vs. 3.3%) and shows a higher rate of distant metastasis within 1 year after the primary site diagnosis (47.8% vs. 23.3%), a worse overall prognosis, more frequent mutations of MYB/MYBL1 (50% vs. 25%) and abnormal upregulation of the phosphatidylinositol-3 kinase (PI3K) pathway. Conclusions Submandibular gland ACC is associated with site-specific early cervical lymph node metastasis and hidden distant metastasis, along with rapid progression and a poor prognosis. A high MYB/MYBL1 mutation rate and abnormal upregulation of the PI3K pathway with MYB involvement were identified.